A Formula to Determine Energy Band Gap in Semiconducting Carbon Nanotubes. (1st January 2019) - Gelao, G.; Marani, R.; Perri, A. G.
Abstract : In this paper we propose a new formula to evaluate in semiconducting Carbon Nanotubes the energy bandgap, i.e. the electronic transition energy from the first valence band to the first conduction band, which is fundamental for electronic applications of CNTs as channel in field effect transistors. The proposed formula is based on empirical correction factors, gained by an optimization procedure aimed at matching experimental data, which results in negligible errors. Moreover the proposed formula shows a new dependence on CNT symmetry indexes (n-m), which has been never observed in literature.